2022
DOI: 10.4155/fmc-2021-0157
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ligases: a Potential Multi-Drug Target for Different Types of Cancers and Neurological Disorders

Abstract: Ubiquitylation is a posttranslational modification of proteins that is necessary for a variety of cellular processes. E1 ubiquitin activating enzyme, E2 ubiquitin conjugating enzyme, and E3 ubiquitin ligase are all involved in transferring ubiquitin to the target substrate to regulate cellular function. The objective of this review is to provide an overview of different aspects of E3 ubiquitin ligases that can lead to major biological system failure in several deadly diseases. The first part of this review cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 129 publications
0
7
0
Order By: Relevance
“…E3 ligases are also involved in the regulation of several diseases including metabolic diseases, cancer, and neurological dysfunction. 60 Therefore, modulating the activities of the E3 ligase can serve as a potential strategy for therapeutic intervention. In 2017, Dr. Ciulli's group reported an approach named homo-PROTACs, which can effectively trigger a VHL E3 ligase suicide-type chemical knockdown inside the cells, 61 and they later report on homobifunctional CRBN degraders that were developed.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E3 ligases are also involved in the regulation of several diseases including metabolic diseases, cancer, and neurological dysfunction. 60 Therefore, modulating the activities of the E3 ligase can serve as a potential strategy for therapeutic intervention. In 2017, Dr. Ciulli's group reported an approach named homo-PROTACs, which can effectively trigger a VHL E3 ligase suicide-type chemical knockdown inside the cells, 61 and they later report on homobifunctional CRBN degraders that were developed.…”
Section: ■ Discussionmentioning
confidence: 99%
“…E3 ubiquitin ligases are the key enzymes within proteostasis, also known as the required component of PROTAC to induce the ubiquitination and subsequent proteasomal degradation of the protein of interest. E3 ligases are also involved in the regulation of several diseases including metabolic diseases, cancer, and neurological dysfunction . Therefore, modulating the activities of the E3 ligase can serve as a potential strategy for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…77 Numerous investigations have focused on the link between E3s and carcinogenesis and concluded that unregulated E3s are essential oncogenes that participate in distinct facets of tumorigenesis, such as survival, proliferation, invasion, and chemoresistance. 78,79 Fbox and WD repeat domain-containing 7 (FBW7) tumor suppressor is a substrate recognition element of the skp cullin f-box (SCF) ubiquitin ligase complex, tuning multiple signalings engaged in tumorigenesis including c-Myc, cyclin-E, mammalian target of rapamycin (mTOR), and Notch. [80][81][82][83][84] FBW7 is frequently inactivated or deleted in diverse cancers such as HCC, CRC, and esophageal squamous cell carcinoma (ESCC).…”
Section: Ubiquitin Ligases (E3s)mentioning
confidence: 99%
“…Indeed, 80% of the population relies on herbal drugs and supplements for their primary healthcare needs (6)(7)(8). In recent decades, approximately half of all pharmaceutical medications have been generated directly or indirectly from the active parts of medicinal plants, putting them at the forefront of drug research initiatives (9,10).…”
Section: Introductionmentioning
confidence: 99%